2010
DOI: 10.1016/j.vetmic.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E virus-specific antibodies in sera of German domestic pigs estimated by using different assays

Abstract: 21Hepatitis E virus is the causative agent of an acute hepatitis in humans. In 22 industrialized countries, autochthonous hepatitis E cases in the past were mainly of 23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
4
42
0
1
Order By: Relevance
“…In studies carried out by Munné et al (2006), a strain of HEV was isolated from pigs in Argentina, showing a high degree of similarity in the nucleotide sequence to HEV strains previously identified in humans with sporadic cases of hepatitis E. In Bolivia, Dell 'Amico et al (2011) observed a positivity of 6.3% (236 patients) using an enzyme-linked immunosorbent assay (IgG anti-HEV), as well as 22.7 and 31.8% of positives by molecular testing for the HEV open reading frame (ORF)-2 in humans and pigs feces, respectively. The high levels of HEV detected in pigs from different countries (Clayson et al, 1995;de Deus et al, 2006;Baechlein et al, 2010) suggests that they could be carriers of HEV, and that this virus is a zoonosis transmitted to humans through water contaminated with pig feces or through contaminated viscera intended for consumption (La Rosa et al, 2010). However, swine HEV infection is asymptomatic; thus, it is difficult to determine when the infection peaks in order to optimize the sensitivity of tests for the virus (Di Bartolo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In studies carried out by Munné et al (2006), a strain of HEV was isolated from pigs in Argentina, showing a high degree of similarity in the nucleotide sequence to HEV strains previously identified in humans with sporadic cases of hepatitis E. In Bolivia, Dell 'Amico et al (2011) observed a positivity of 6.3% (236 patients) using an enzyme-linked immunosorbent assay (IgG anti-HEV), as well as 22.7 and 31.8% of positives by molecular testing for the HEV open reading frame (ORF)-2 in humans and pigs feces, respectively. The high levels of HEV detected in pigs from different countries (Clayson et al, 1995;de Deus et al, 2006;Baechlein et al, 2010) suggests that they could be carriers of HEV, and that this virus is a zoonosis transmitted to humans through water contaminated with pig feces or through contaminated viscera intended for consumption (La Rosa et al, 2010). However, swine HEV infection is asymptomatic; thus, it is difficult to determine when the infection peaks in order to optimize the sensitivity of tests for the virus (Di Bartolo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even though commercial assays for detection of anti-HEV antibodies in humans, which are based on proteins of gt1 and/or gt2, are available, there are still concerns about their utility for infections caused by other genotypes (2,3,14,20,28). In addition, they are not designed to be used with samples from swine, a likely natural reservoir of HEV (29).…”
Section: Discussionmentioning
confidence: 99%
“…HEV is classified into four genotypes (gt) that infect humans, although only gt3 and gt4 have been isolated in other animal species, mainly pigs (2,6,29,36) and, recently, rats (21,23,37). HEV is enterically transmitted and causes epidemic outbreaks in areas with inadequate hygienic conditions and/or water supplies, and thus, it has become an important public health concern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The virus is ubiquitous in the domestic pig and wild boar population in several European countries. In Germany, a high wild boar percentage was proven to be infected with HEV [13,14,15]. …”
Section: Introductionmentioning
confidence: 99%